2015
DOI: 10.1002/jcp.25021
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Zinc Finger 1 (MZF‐1) Regulates Expression of the CCN2/CTGF and CCN3/NOV Genes in the Hematopoietic Compartment

Abstract: Connective Tissue Growth Factor (CCN2/CTGF) and Nephroblastoma Overexpressed (CCN3/NOV) execute key functions within the hematopoietic compartment. Both are abundant in the bone marrow stroma, which is a niche for hematopoiesis and supports marrow function. Roles for 1,25-dihydroxyvitamin D3 (calcitriol) and all-trans retinoic acid in the bone marrow have also been elucidated. Interestingly, some of the annotated roles of these vitamins overlap with established functions of CCN2 and CCN3. Yet, no factor has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the present study, the CpG 2–4 and CpG17–18 were all located within 100 bp of the TSS. The CpG 2–4 and CpG 17–18 co-localise with 3 putative transcription factors, which are involved in cell proliferation and differentiation (TFAP2A) [ 23 ], cell cycle (E2F4) [ 24 ] and hematopoiesis (MZF1) [ 25 ]. We also found that an experimentally validated transcription factor ELK1 was bound to CpG 6, which was located 19 bp upstream of TSS and 24 bp downstream of CpG 2–4, and had higher methylation in benzene-exposed workers than unexposed controls, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the CpG 2–4 and CpG17–18 were all located within 100 bp of the TSS. The CpG 2–4 and CpG 17–18 co-localise with 3 putative transcription factors, which are involved in cell proliferation and differentiation (TFAP2A) [ 23 ], cell cycle (E2F4) [ 24 ] and hematopoiesis (MZF1) [ 25 ]. We also found that an experimentally validated transcription factor ELK1 was bound to CpG 6, which was located 19 bp upstream of TSS and 24 bp downstream of CpG 2–4, and had higher methylation in benzene-exposed workers than unexposed controls, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…18 Myeloid zinc finger 1 (MZF1) is a transcription factor of many genes ie c-Myc, connective tissue growth factor (CTGF), and MZF1 can obviously promote cell proliferation and ECM synthesis. [19][20][21] In the initial stage of this study, we not only revealed a potential MZF1-binding site in the promoter of RGC-32 gene, but also proved that the MZF1 expression increased simultaneously with RGC-32 both in vivo and in vitro. Therefore, the role of MZF1 and the relationship between MZF1 and RGC-32 in GMC proliferation and ECM production upon sublytic C5b-9 stimulation need to be clarified.…”
Section: Introductionmentioning
confidence: 52%
“…As we know, gene expression is often regulated by special transcriptional factors . Myeloid zinc finger 1 (MZF1) is a transcription factor of many genes ie c‐Myc, connective tissue growth factor (CTGF), and MZF1 can obviously promote cell proliferation and ECM synthesis . In the initial stage of this study, we not only revealed a potential MZF1‐binding site in the promoter of RGC‐32 gene, but also proved that the MZF1 expression increased simultaneously with RGC‐32 both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Myeloid Zinc Finger 1 (MZF‐1) is a hematopoietic transcription factor found in several cell types to interact with the CCN3 promoter and regulate the expression of CCN3. Notably, vitamin D3 and trans‐retinoic acid can induce the upregulation of CCN3 by MZF‐1 (Piszczatowski et al 2015). Several studies have identified the post‐transcriptional regulation of CCN3 by several micro RNAs (miRNAs).…”
Section: The Expression Regulation Mechanism Of Ccn3mentioning
confidence: 99%